Комическая фантазия: пьесы / Григорий Горин - Горин Григорий Израилевич (Советский писатель, 1986)
Экземпляры: КХ (20120706) / Инвентарный номер: 875844 / Цена: 1.90 / Сис.шифр: Р2 / Авт.знак: Г 69 / ГРНТИ: 17 / ББК: 84(2)